A new species of Chimarra from China (Trichoptera, Philopotamidae) with description of its larva - Hu, Yan-Li; Wang, Bei-Xin; Sun, Chang-Hai (Zootaxa, 2018)
The adult male and larva of a new species in the genus Chimarra Stephens, Chimarra paramonorum n. sp., are described, diagnosed, and illustrated based on the specimens collected in Zhejiang Province, China. The larva and adult male were associated by mtCOI gene sequences. The male can be separated from C. monorum and C. thienemanni mainly by small preanal appendages and by wrinkled, hairless endotheca. The larva of the new species can be separated from other congeners by a combination of characters including the notch on the anterior margin of the frontoclypeus, the teeth of the mandibles, and the length of the seta-bearing process of each forecoxa. The larval description is the first for Chimarra in China.